2008
DOI: 10.1179/174329308x380354
|View full text |Cite
|
Sign up to set email alerts
|

Study on metal transfer modes and welding spatter characteristics of self-shielded flux cored wire

Abstract: The metal transfer behaviour of self-shielded flux cored wire and the resultant welding spatter were investigated by using a high speed camera. Three modes of metal transfer were found, i.e. bridging transfer without arc interruption in explosive form or by surface tension, globular repelled transfer and droplet transfer, while the former two modes played a key role in the weld metal transfer. Correspondingly, the bridge explosion, discontinuous globular repelled process and the misalignment of droplets transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For example, though the spatter issue occurs when the swing arc is introduced [23], it has not attracted the attention of researchers. As is well known, welding spattering can lead to problems such as low wire utilization, poor bead formation, poor mechanical performance of the obtained joints and an extensive post-cleaning process [24][25][26]. In the multi-layer and multi-pass WAAM process, the spatter on the deposited pass is extremely detrimental to the deposition process stability of the subsequent pass and eventually to the performance of the WAAM component.…”
Section: Introductionmentioning
confidence: 99%
“…For example, though the spatter issue occurs when the swing arc is introduced [23], it has not attracted the attention of researchers. As is well known, welding spattering can lead to problems such as low wire utilization, poor bead formation, poor mechanical performance of the obtained joints and an extensive post-cleaning process [24][25][26]. In the multi-layer and multi-pass WAAM process, the spatter on the deposited pass is extremely detrimental to the deposition process stability of the subsequent pass and eventually to the performance of the WAAM component.…”
Section: Introductionmentioning
confidence: 99%
“…Łabanowski et al used the gas metal arc (GMA) local dry welding method to make welded joints of duplex stainless steel, which proved that duplex stainless steel had a good underwater local dry welding property [22]. Liu et al researched the metal transfer behavior of self-shielded flux-cored wire and found that the metal transfer mode included bridging transfer, globular repelled transfer, and droplet transfer [23]. Guo et al observed the metal transfer process of underwater flux-cored wet welding using an X-ray transmission method, and found four fundamental metal transfer modes, namely, the globular repelled transfer mode, the surface tension transfer mode, the explosive short-circuit transfer mode, and the “submerged arc transfer mode” [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The main modes of molten droplet transfer in FCAW-S are short-circuit enclosed slag transfer without explosion, short-circuit transfer with explosion, short-circuit swaying outward transfer, globular transfer, projected transfer, explosive transfer, 5 and bridging transfer without arc interruption. 6, 7 In CO 2 gas shielded metal arc welding, the short-circuit transfer is an excellent transfer mode for its process stability, lesser welding spatter and low heat input. However, during the short-circuit transfer process in FCAW-S, the liquid slag covers the surface of the molten droplet and the weld pool, which increases the difficulty of arc re-ignition.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in arc voltage, the ratio of short-circuit transfer with explosion and globular transfer increases. Yu et al 6 finds that the short-circuit and non-short-circuit enclosed slag transfer are the main transfer modes when arc voltage is lower. With an increase in arc voltage, the ratio of non-short-circuit enclosed slag transfer increases and the ratio of short-circuit enclosed slag transfer decreases.…”
Section: Introductionmentioning
confidence: 99%